Comparative study of energy harvesting performance of magnetoelectric composite-based piezoelectric beams subject to varying magnetic field. (1st October 2022) - Ren, Zhuang; Tang, Lihua; Zhao, Jiucheng; Zhang, Shizhong; Liu, Changyi; Zhao, Hongwei
Abstract: Magnetostrictive materials with good mechanical properties can effectively convert the alternating magnetic energy in the environment into mechanical vibrations via the magnetostriction effect. Few studies exist on the working mechanism and the effect on the performance of magnetoelectric (ME) composite components in complex magnetic field environments. This work first investigated the magnetoelectric conversion process of two types of ME composite components under the action of DC magnetic field alone and the DC–AC coupled magnetic field using COMSOL simulation. When coupled with AC magnetic field, the DC bias magnetic field can enhance the magnetization by AC field for the Galfenol alloy component and negate the magnetization for the nickel component. Then, two types of ME composite components made from Galfenol alloy and nickel bonded with piezoelectric transducer are prototyped and tested for energy harvesting. The experimental results show that, under a harmonic excitation of 3 Oe magnetic field, the DC bias magnetic field of 120 Oe can increase the open-circuit voltage of the Galfenol alloy based harvester from 0.495 V to 10.68 V, and the output power from 1.6 μ W to 42 μ W by 2525% with a matched external resistance of 50 kΩ. Under the same amplitude of AC magnetic field, the DC bias magnetic field increases the open-circuit voltage of the nickel based harvester from 0.117 V to 0.837 V, and the output power from 2.6 μ W to 23 μ W by 784.6% with a matched resistance of 1000 kΩ. The findings of this work reveal the effect of the coupled magnetic field for the magnetostriction for different magnetostrictive materials and provide the guideline for the design of magnet electric energy harvesters.